Legal Politics of Film Censorship in Indonesia: From the Dutch East Indies Colonial Era to the New Order - Sofyan Hadi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Film censorship in Indonesia has a long historical trajectory, reflecting the intricate relationship between political power and legal frameworks governing public entertainment. This study examines how ruling governments across different historical periods employed legal politics to control film content, and how political determination shaped censorship law. Utilizing a normative juridical methodology with statutory and historical approaches, the research analyzes primary legal materials—including the Film Ordonantie of 1916 with its seven amendments, Japanese military regulations, and national legislation up to Law No. 8/1992 on Film. The theoretical framework integrates Lawrence Friedman's legal system theory and Mahfud MD's political determination thesis. Findings reveal that film was consistently perceived as a strategic propaganda instrument rather than merely a cultural product, leading to policies designed to protect ruling interests. The Dutch East Indies prioritized maintaining white prestige, the Japanese military served war objectives, the Old Order witnessed ideological contestation, and the New Order enforced development narratives alongside anti-communism campaigns. Throughout these periods, political configurations significantly determined the substance, structure, and legal culture of censorship institutions, confirming the determinative influence of politics on law. Ultimately, this study contributes to legal history scholarship by providing a comprehensive analysis of film censorship evolution in Indonesia. Keywords: Film Censorship; Legal Politics; Colonial Law; New Order; Propaganda; Legal History; Indonesian Cinema